Modification of multiwall carbon nanotube by thiol-ene click chemistry - Temel, Gokhan; Uygun, Mustafa; Arsu, Nergis (SPRINGER, 2013)
Thiol-ene click chemistry was used for the preparation of polystyrene grafted multiwall carbon nanotubes (MWCNTs) via the thermal initiation method. The thiol end-functional PSt (PSt-SH) was prepared by the nucleophilic substitution reaction of the bromide end groups of PSt obtained by atom transfer radical polymerization. PSt-SH grafted to the surface of the MWCNTs by thiol-ene click chemistry via the thermal initiation method.
Keywords: Carbon nanotube; Click chemistry; Functionalization; Thiol-ene; TRANSFER RADICAL POLYMERIZATION; TELECHELIC POLYMERS; DIELS-ALDER; POLYSTYRENE; COMBINATION; COPOLYMERS; BLOCK; PHOTOINITIATOR; ATRP; Polymer Science